2005
DOI: 10.1016/j.chembiol.2004.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Highly Selective Inhibition of MMP-13

Abstract: Inhibitors for matrix metalloproteinases (MMPs) are under investigation for the treatment of cancer, arthritis, and cardiovascular disease. Here, we report a class of highly selective MMP-13 inhibitors (pyrimidine dicarboxamides) that exhibit no detectable activity against other MMPs. The high-resolution X-ray structures of three molecules of this series bound to MMP-13 reveal a novel binding mode characterized by the absence of interactions between the inhibitors and the catalytic zinc. The inhibitors bind in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
216
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(225 citation statements)
references
References 43 publications
3
216
1
4
Order By: Relevance
“…The specificity loop has often been focused as a hotspot for selective MMP inhibitors because of its high sequence and length variability in different MMPs. Pyrimidine dicarboxamide derivatives are notable examples with low-nanomolar affinity for MMP-13, interacting only with the unique S1′ pocket but not touching the catalytic zinc at all (25).…”
Section: Resultsmentioning
confidence: 99%
“…The specificity loop has often been focused as a hotspot for selective MMP inhibitors because of its high sequence and length variability in different MMPs. Pyrimidine dicarboxamide derivatives are notable examples with low-nanomolar affinity for MMP-13, interacting only with the unique S1′ pocket but not touching the catalytic zinc at all (25).…”
Section: Resultsmentioning
confidence: 99%
“…A novel subnanomolar nonchelating MMP13 inhibitor was also reported that binds deeply into the S 1 0 pocket of MMP13 and protrudes into the S 1 0 * side pocket. In this bent conformation, it clamps around a leucyl side chain, which is unique to MMP13 (Engel et al, 2005). However, it is not clear whether these are true allosteric inhibitors or functioning by competing for S 1 0 subsite occupancy in deep pocket MMPs.…”
Section: Exosite Binding and Allosteric Inhibitorsmentioning
confidence: 99%
“…544678-85-5)] was dissolved in DMSO and added with each medium replacement to a final concentration of 10 M; the same volume of DMSO without inhibitor was added to the control cells. This inhibitor has high specificity for MMP-13 and binds to the catalytic domain (8). To inhibit MMP-2 activity, MMP-2 inhibitor [IUPAC name 2-((isopropoxy)-(1,1=-biphenyl-4-ylsulfonyl)-amino))-N-hydroxyacetamide (catalog no.…”
Section: Muscle Injury Modelsmentioning
confidence: 99%